Perceptions of Telemental Health Care Delivery During COVID-19: A Cross-Sectional Study With Providers, February-March 2021 - Wilczewski, Hattie; Paige, Samantha R.; Ong, Triton; Barrera, Janelle F.; Soni, Hiral; Welch, Brandon M.; Bunnell, Brian E. (Frontiers in Psychiatry, 2022)
The COVID-19 pandemic accelerated adoption of telemental health (TMH). Providers with limited TMH experience faced challenges during the rapid switch to remote patient care. We investigated TMH providers’ perceptions about remote care one year into the pandemic according to when providers adopted telemedicine (i.e., before vs. after March 2020) and how much of their caseloads were served remotely (i.e., <50% vs. ≥50%). Between February-March 2021, 472 TMH providers completed a cross-sectional, web-based survey that measured perceived benefits and satisfaction with telemedicine, therapeutic alliance, patient-centered communication, eHealth literacy, multicultural counseling self-efficacy, and facilitating factors of using telemedicine. Providers who began using telemedicine before the pandemic reported having better training, task-related therapeutic alliance with patients, and ability to conduct multicultural interventions, assessments, and session management. Providers who served ≥50% of their caseload remotely reported greater satisfaction with their practice, stronger beliefs about the benefits of telemedicine, and greater perceived effects of telemedicine on alleviating the impact of COVID-19. There were no differences in reports of patient-centered communication nor eHealth literacy. In conclusion, providers who adopted TMH more recently may require additional training and support to successfully establish a working alliance with their patients, especially those who are multicultural.